Aislamiento y selección de cultivos nativos de Bacillus sp. productores de proteasas a partir de compost, Trujillo – Perú. - Carranza Vega, Dark Vádher (2017)
Alkaline proteases are a physiologically and commercially important group, used primarily as detergent additives and food processing. The objective of this research was to isolate and select native Bacillus sp. Protease producers from compost of the Experimental Station of Applied Biochemistry, National University of Trujillo, Perú. For this purpose, compost was collected as a sample, enriched with a 1% casein solution, and a thermal treatment (80 °C for 15 minutes). To isolate the native Bacillus, serial dilutions were made, and 0.1 mL per surface were plated on Casein Agar plates and incubated at 37 ° C for 24 to 48 hours. The selected bacterial cultures were placed in stirred system bioreactors containing Casein Broth at room temperature (23 ° C - 25 ° C), and every 24 hours (0, 24, 48, 72, 96, 120 and 144 h) was determined the production of proteases by extracting 8 mL of sample from each bioreactor and centrifuged. To the separated supernatant, the amount of proteases produced in relation to the incubation time was measured by measuring the residual casein and the enzymatic activity of the proteases was determined by the Sharmin and Rahman method. Of the 23 isolated bacterial cultures, 02, Culture FGM-02DL and Culture FGM-17DL were selected, as they had a halo diameter of hydrolysis of 3.3 cm and 3.7 cm, respectively. These cultures had colonies with a size of 3 to 4 mm, rounded, convex elevation, irregular edges, dry appearance as frosted glass, beige - light beige, and microscopically Gram (+) bacilli, with spherical wavelengths and Position. Statistical analysis of the average enzyme units (EU / mL) of FGM-02DL and FGM-17DL cultures showed no significant difference (p> 0.05), which leads to the conclusion that both selected bacterial cultures have the same hydrolytic capacity over casein.